PENGARUH TALENTA, SEMANGAT DAN BISNIS ONLINE TERHADAP KINERJA UKM DI PERKAMPUNGAN INDUSTRI KECIL JAKARTA TIMUR - Sukardi; Crysthal Indah Marina (Jurnal Manajemen Bisnis Krisnadwipayana, 2020)
Research objectives to determine whether talent, semangat and online business (e-commerce) affect the performance of the Industrial Small community, East Jakarta. This type of research uses a quantitative approach. The survey method used was through distributing questionnaires to business owners in the east Jakarta area. The technique of determining the number of samples used the Slovin formula, the sampling used was simple random sampling. The analysis tool used is multiple linear regression. The results showed that the variables of talent, semangat, online business (e-commerce) as a whole partially or simultaneously have a positive and significant effect on the performance.